STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL DI SMP NEGERI 1 SASAK RANAH PASISIE PASAMAN BARAT - Jaswir Jaswir; Dasrizal Dahlan; Rahmi Rahmi (FiTUA: Jurnal Studi Islam, 2022)
This research was backgrounded by the diversity of students at SMP 1 Sasak Alam Pasisie, both from religions, tribes and languages. Plurality is a wealth in itself because with differences we will become more understanding that harmonious coexistence is a necessity, students must be accustomed to starting from the educational environment, namely school. For this reason, it is necessary to know the teacher's strategy in applying pai learning materials with a multicultural basis. The focus of his research is the implementation of Multicultural-Based PAI Learning at SMP 1 Sasak Alam Pasisie. The purpose of this study is to analyze and describe the evaluation of multicultural-based PAI learning at SMP 1 Sasak Alam Pasisie. This research uses observation techniques, documentation and interviews. For analysis techniques, use data reduction techniques, data display and drawing conclusions. The results of this study are that students at SMP 1 Sasak Alam Pasisie have shown satisfactory learning results judging from written test scores that reach KKM standards and in associating with friends of different religions and tribes have a very good tolerance attitude.